The Effect of Omnibus Law Technique on the Quality of Criminal Legislative Drafting in Indonesia - Setiawan, Risman (Yayasan Cahaya Generasi Positif, 2025)
This research critically analyzes the influence of the omnibus law technique on the quality of criminal law formulation in Indonesia, particularly following the enactment of Law No. 13 of 2022 regarding Amendments to Law No. 12 of 2011 on the Formation of Legislation. Although the omnibus law method formally recognizes the integration of multiple legal substances within a single statute to enhance legislative efficiency and regulatory synchronization, empirical evidence demonstrates that its application in the criminal law domain creates serious substantive and procedural challenges. The research employs a normative legal approach supplemented by conceptual analysis to examine the alignment between omnibus law practices and the principles of good legislation (good legislation principles) as stipulated in Article 5 of Law No. 13 of 2022. The findings reveal that while omnibus law offers administrative efficiency, its implementation in criminal legislation generates significant problems regarding norm clarity, public participation, and legal legitimacy. Specifically, the technique tends to obscure the principle of legality (nullum crimen sine lege), reduce deliberative quality in legislative processes due to executive dominance, and weaken public participation in legislative procedures. Furthermore, the rapid processing of omnibus bills with limited public consultation compromises the substantive legitimacy of resulting criminal law provisions. This research concludes that implementing omnibus law techniques in criminal legislation must be accompanied by reinforced mechanisms for meaningful public participation, enhanced transparency in legislative discussions, and rigorous norm quality testing prior to enactment. Without such safeguards, the legislative innovation intended to simplify legal frameworks risks creating new legal uncertainty within Indonesia's national criminal justice system. The research advocates for either restricting omnibus law application to non-criminal legislation or fundamentally restructuring its procedural framework to comply with constitutional standards of democratic lawmaking.